1997
DOI: 10.1021/jo9622791
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Marcfortine A to Paraherquamide A via Paraherquamide B. The First Formal Synthesis of Paraherquamide A

Abstract: The paraherquamides and marcfortines represent a novel class of anthelmintics. The sole structural difference between paraherquamide A and marcfortine A occurs in ring G. We synthesized paraherquamide B from marcfortine A in six steps. Paraherquamide A was then prepared from paraherquamide B in seven steps. This represents the first formal synthesis of paraherquamide A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…The ketones can be reduced further for the construction of cyclic compounds or 1,3‐diols (Scheme ). The reaction also worked well for α,β‐epoxyamides 29d…”
Section: Epoxide Oxetane and Aziridine Opening Through Generatiomentioning
confidence: 89%
“…The ketones can be reduced further for the construction of cyclic compounds or 1,3‐diols (Scheme ). The reaction also worked well for α,β‐epoxyamides 29d…”
Section: Epoxide Oxetane and Aziridine Opening Through Generatiomentioning
confidence: 89%
“…112,113) This intermediate has been previously described by a Pharmacia-Upjohn group, obtained semi-synthetically from marcfortine A. The final step, methyl Grignard addition to the ketone group of 180 has been previously described to give paraherquamide A along with a trace of the corresponding C-14 epimer in ca.…”
Section: )mentioning
confidence: 98%
“…89,90) Industrial interest in the biosynthesis of marcfortine A, which does not display the potency that paraherquamide A possesses, is presumably due to the report from the Pharmacia and Upjohn group demonstrating that marcfortine A can be semi-synthetically converted into paraherquamide A. 91) Kuo et al, found that marcfortine is derived from L-tryptophan (oxindole moiety), L-methionine (via SAM methylation at the g-N; C29), L-lysine (pipecolic acid residue) and acetate (isoprene units) (Chart 26). 82,83) These results clearly demonstrate that the isoprene moieties are of mevalonate origin.…”
Section: The Paraherquamides Marcfortines and Related Alkaloidsmentioning
confidence: 99%
“…Nach Epoxidöffnung unter protischen Bedingungen können die Ketone zur Herstellung von cyclischen Verbindungen oder 1,3‐Diolen verwendet werden (Schema ). α,β‐Epoxyamide erwiesen sich ebenfalls als geeignete Edukte für den Elektronentransfer 29d…”
Section: Epoxid‐ Oxetan‐ Und Aziridinöffnung Durch Bildung Der Enunclassified